STRATEGI PENGEMBANGAN EKOWISATA DI TAMAN NASIONAL KELIMUTU - Rudi Hermawan; Arief Chandra; Persada Agussetia Sitepu (Jurnal Belantara, 2019)
Ecotourism development strategy in Kelimutu National Park (KNP) is very necessary because KNP has enormous potential for ecotourism development. The potential is either in the form of flora, fauna, geology, environmental beauty, and cultural potential of the surrounding community. The aims of this study are to know the right strategy in ecotourism development and determine the priority scale of ecotourism pathways development in KNP. This study uses a case study approach. Data were collected through in-depth interviews of KNP management, stakeholders in the management of ecotourism of KNP, communities around KNP, and observation. The data were analyzed using stakeholders analysis to determine the stakholders that involved on ecotourism management in KNP, SWOT (Strength, Weakness, Opportunities, Threats) analysis to determine the right strategy in ecotourism management, and AHP (Analysis Hierarcy Process) to determine the priority scale of ecotourism development from several ecotourism pathway in KNP. The results show that the most appropriate strategy in the development of ecotourism in KNP is offensive strategy (taking advantage of opportunities and strengths owned), and ecotourism pathway that get the first priority to be developed is the Moni Pathway, the second is Wologai Pathway, the third is Sokoria Pathway, and the fourth is Niowula Pathway.